Estudo da mecânica clássica e aplicações em sistemas celestes - Morini, Bruno Henrique [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
In this study we investigate, using the software “Atomic/Molecular Massively Parallel Simulator” (LAMMPS), the possibility of constructing a numerical description for gravitationally interacting particles. Such description was constructed through a mathematical mapping between the Coulomb's potential and the gravitational potential, based on the methods described by Füglistaler, recently. First, the analytical techniques of classical mechanics were discussed, through the perspective of Newton, Lagrange and Hamilton. Then, an adaptation of the Coulomb's potential of LAMMPS code was constructed in order to allow the description of gravitational interactions, which was the main goal of the present study. The construction of the bodies considered during the simulations performed were achieved using a method known as Fibonacci lattice, which allows the construction of granular bodies with constant density. MacCullag's equation was used to obtain an analytical description of the gravitational potential of an ellipsoidal continuous body in order to make it possible to perform comparisons against the potential of a granular body. During the simulations using the adapted potential, the conservative character of the systems was tested. Simulations of orbits between two bodies were performed, observing the behavior of total energy and total angular momentum of the systems of interest. Then, the potentials in the surroundings of several bodies with different granularities and with spherical, oblate and prolate shapes were mapped. For orbits between two bodies, we saw that the total energy and total angular momentum are constant along the orbit, which demonstrates that the system is conservative over time. In the comparison between the two methods used for mapping the potential, decreasing the granularity of the bodies caused a fast decrease on the difference between the results of each method, indicating a fast convergence. We have seen that the potential depends on the shape of the body and, as in the case of granularity, the error decays rapidly with distance.

Nesse trabalho investigamos, utilizando o software “Atomic/Molecular Massively Parallel Simulator” (LAMMPS), a possibilidade de construir uma descrição numérica para partículas interagindo gravitacionalmente. Tal descrição foi construída através de um mapeamento matemático entre o potencial coulombiano e o potencial gravitacional, utilizando como motivação os métodos descritos recentemente por Füglistaler. Primeira- mente, foram discutidas as técnicas analíticas da mecânica clássica, através da perspectiva de Newton, Lagrange e Hamilton. Em seguida, foi realizada a adaptação do potencial coulombiano implementado no código LAMMPS para que este seja capaz de descrever interações gravitacionais, que era o objetivo do trabalho. Os corpos utilizados durante as simulações realizadas foram construídos utilizando o método do lattice de Fibonacci, que possibilita a construção de corpos granulares com densidade constante. A equação de MacCullag foi utilizada para obter uma descrição analítica de um corpo contínuo elipsoidal, com a finalidade de possibilitar comparações com o potencial de um corpo granular. Durante as simulações utilizando o potencial adaptado o caráter conservativo do sistema foi testado. Para isso, foram realizadas simulações de órbitas entre dois corpos, observado o comportamento da energia total e do momento angular total do sistema. Em seguida, foram mapeados os potenciais nas redondezas de diversos corpos com diferentes granulosidades e com formatos esféricos, oblatos e prolatos. Para órbita entre dois corpos, vimos que a energia total e momento angular total são constantes ao longo da órbita o que demonstra que o sistema é conservativo ao longo do tempo. Na comparação entre os dois métodos utilizados para o mapeamento do potencial, ao se diminuir a granulosidade dos corpos, a divergência entre os métodos decai rapidamente, indicando uma rápida convergência. Vimos que o potencial tem dependência do formato do corpo e como no caso da granulosidade o erro decai rapidamente com a distância.
Study of classical mechanics and applications in celestial systems
Keywords: Simulations; Potentials; Gravitation; Simulações; Potenciais; Gravitação